2014
DOI: 10.2478/rrlm-2014-0011
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of resistin predict cardiovascular events

Abstract: Background: A number of cytokines and adipokines secreted by adipose tissue may influence vessel wall directly. Adiponectin exhibits anti-inflammatory and atheroprotective actions. Resistin is expressed at higher levels in inflammatory cells. Resistin directly activates the endothelium through upreglation of adhesion molecules, induces production of TNF-α by macrophages, effects that are antagonized by adiponectin. Leptin has multiple effects on cells of artery walls, many similar to those of resistin. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Studies have also identified resistin levels in patients with overt peripheral atherosclerosis. In one study, these were elevated in patients with peripheral arterial disease (PAD) compared to those with ischemic heart disease [ 86 ] and plasma levels of resistin and diastolic BP were predictors of new ischemic events and readmission for nonfatal myocardial infarction, heart failure, or critical limb ischemia in these patients. Moreover, in patients with PAD who underwent bypass surgery, increased levels of resistin were able to predict the reduced free survival range without amputation in patients with critical limb ischemia, regardless of the presence of diabetes [ 87 ].…”
Section: Adipokines As Biomarkers In Atherosclerotic Heart Diseasementioning
confidence: 99%
“…Studies have also identified resistin levels in patients with overt peripheral atherosclerosis. In one study, these were elevated in patients with peripheral arterial disease (PAD) compared to those with ischemic heart disease [ 86 ] and plasma levels of resistin and diastolic BP were predictors of new ischemic events and readmission for nonfatal myocardial infarction, heart failure, or critical limb ischemia in these patients. Moreover, in patients with PAD who underwent bypass surgery, increased levels of resistin were able to predict the reduced free survival range without amputation in patients with critical limb ischemia, regardless of the presence of diabetes [ 87 ].…”
Section: Adipokines As Biomarkers In Atherosclerotic Heart Diseasementioning
confidence: 99%
“…The apelin and its receptor (APJ receptor) is one of the molecular systems which counteracts the negative effects of aldosterone on the myocardial cells and limits the inflammatory reactions and the oxidative stress that are increased in chronic, severe, heart failure. Although apelin is also synthesized in the adipose tissue and was listed as adipocytokine and studied as one [8][9][10][11], its major site of synthesis and target is the endothelium and the cardiovascular system. It is the most potent endogenic positive inotropic agent and is a positive regulator of angiotensin converting enzyme type 2, and so it is a RAAS antagonist [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with heart failure an inverse correlation between leptin and mortality was found, suggesting a protective role of leptin [ 27 ]. In severe and end stage cachectic heart failure the plasma levels of leptin have been shown to be lower as compared with non-cachectic heart failure patients [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%